Seasonal patterns in rainforest litterfall: Detecting endogenous and environmental influences from long‐term sampling. (8th November 2017) - Edwards, Will; Liddell, Michael J.; Franks, Peter; Nichols, Cassandra; Laurance, Susan G. W.
Abstract: Tropical rainforests play an important role in the storage and cycling of global terrestrial carbon. In the carbon cycle, net primary productivity of forests is linked to soil respiration through the production and decomposition of forest litter. Climate seasonality appears to influence the production of litter although there is considerable variability within and across forests that makes accurate estimates challenging. We explored the effects of climate seasonality on litterfall dynamics in a lowland humid rainforest over a 7‐year period from 2007 to 2013, including an El Niño/La Niña cycle in 2010/2011. Litterfall was sampled fortnightly in 24 traps of 0.50 m diameter within a 1‐ha forest plot. Total mean litterfall was 10.48 ± 1.32 (±SD, dry weight) Mg ha −1 year −1 and seasonal in distribution. The different components of litterfall were divided into L Leaf (63.5%), L Wood (27.7%) and L FF[flowers & fruit] (8.8%), which all demonstrated seasonal dynamics. Peak falls in L Leaf and L Wood were highly predictable, coinciding with maximum daily temperatures and 1 and 2 months prior to maximum monthly rainfall. The El Niño/La Niña cycle coincided with elevated local winter temperatures and peak falls of L Leaf and L Wood . Importantly, we establish how sampling length and generalized additive models eliminate the requirement for extensive within‐site sampling when the intention is to describe dynamics in litterfall patterns. Further, a greater understanding of seasonal cycles in litterfall allows us to distinguish between endogenous controls and environmental factors, such as El Niño events, which may have significant impacts on biochemical cycles.